Hubungan Status Ekonomi Keluarga Dengan Status Gizi Balita Di Kecamatan Ajung Kabupaten Jember Tahun 2016: The Relationship Between Family Economic Status and Nutritional Status of Toddlers in Ajung Subdistrict, Jember Regency, in 2016 - Yuli Indarti (Fenomena, 2016)
Protein-energy malnutrition remains a major public health challenge in Indonesia, with a prevalence of under-five malnutrition reaching 19.6% in 2013. This study aimed to identify the relationship between family economic status, number of children, and maternal education on the nutritional status of children under five. A quantitative study using a cross-sectional design was conducted in Ajung Sub-District, Jember Regency, involving 214 children under five selected through multistage cluster random sampling. Data were analyzed using the Chi-Square test. The results showed a significant relationship between family economic status and the nutritional status of children under five (calculated X² = 4.639 > table X² = 3.841), as well as a significant relationship between maternal education and children's nutritional status. In contrast, the number of children in the family did not show a meaningful relationship. This study concludes that family economic factors and maternal education are important determinants of the nutritional status of children under five, thus interventions to increase family income and maternal education should be prioritized in community-based nutrition programs. Masalah gizi buruk dan kurang energi protein masih menjadi tantangan utama kesehatan masyarakat di Indonesia, dengan prevalensi gizi kurang pada balita mencapai 19,6% pada tahun 2013. Penelitian ini bertujuan untuk mengidentifikasi hubungan antara status ekonomi keluarga, jumlah anak, dan pendidikan ibu terhadap status gizi balita. Penelitian kuantitatif dengan desain cross sectional ini dilakukan di Kecamatan Ajung, Kabupaten Jember, melibatkan 214 balita yang dipilih melalui multistage cluster random sampling. Analisis data menggunakan uji Chi-Square. Hasil penelitian menunjukkan adanya hubungan signifikan antara status ekonomi keluarga dengan status gizi balita (X² hitung = 4,639 > X² tabel = 3,841), serta hubungan signifikan antara pendidikan ibu dengan status gizi balita. Sebaliknya, jumlah anak dalam keluarga tidak menunjukkan hubungan yang bermakna. Penelitian ini menyimpulkan bahwa faktor ekonomi keluarga dan pendidikan ibu merupakan determinan penting status gizi balita, sehingga intervensi peningkatan pendapatan keluarga dan pendidikan ibu perlu menjadi prioritas program gizi berbasis komunitas.